Avaliação do Programa de Apoio ao Desenvolvimento Infantil (PADIN) aplicado à formação dos agentes de desenvolvimento infantil no Município de Itapiúna-CE - Fernandes, Vanessa Benício Lima (2025)
The Child Development Support Program (Padin), created in 2015, is part of the "Time to Grow" pillar of the Mais Infância Ceará Public Policy (Ordinary Law No. 17,380, January 5, 2021), covering all 184 municipalities in Ceará and serving children from zero to 5 years and 11 months. The program aims to ensure the integral development of children in Ceará, offering support to families and creating conditions that promote quality of life in early childhood. Recognizing childhood as a historical and social construct, as analyzed by Philippe Ariès (1978), this research starts from the understanding that the perception of childhood has evolved over the centuries, recognizing children as rights holders and as individuals requiring specific care and protection. Thus, this study aims to evaluate the continuing education offered by Padin to Child Development Agents (ADIs) in the municipality of Itapiúna, from its implementation in 2017 until 2024. Using a qualitative, exploratory, and descriptive approach, the research employed data collection instruments such as document analysis of materials produced by the Ceará State Department of Education (Seduc), field diary records from training meetings, and semi-structured interviews with local ADIs. The methodology was based on In-Depth Evaluation (Rodrigues, 2008), covering four analytical axes: program content analysis, investigation of the policy formulation context, monitoring of the program’s institutional trajectory, and evaluation of its temporal and territorial scope. The findings revealed that the continuing education provided by Padin has been relevant for the professional development of the ADIs, offering theoretical and practical tools to improve their home visit interventions. However, the results also highlight the need for further training on topics such as inclusion and social vulnerability, as well as the expansion of practical monitoring strategies, to strengthen the agents' capacity to deal with the complex realities of the families served by the program.